Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages given rise to a general septicaemia. A tremendous number of man-hours are lost every year from poisoned hands by the neglect to look after small scratches and cuts. For one large industrial organization in this country, the incidence of sepsis fell on the introduction of a medical service from 3 per cent to approximately 0.5 per cent in one year. At the end of five years it had gradually declined to 0.2 per cent. Many workers are very much prejudiced against compulsory medical examination by a works doctor. It is quite true that there are objections, some of a serious nature, but to-day these objections should not weigh against the need to utilize every possible scientific method to increase output. It is not possible to deal with the many industrial diseases that could be got rid of by an efficient industrial medical service, but a word should be said about tuberculosis. More young women between the ages of 18 and 24 die from this disease than from any other, and both the death-rate and the number of new cases recorded have risen seriously since the outbreak of war.* It is not appreciated enough that the majority of early detected cases of this disease are easily cured. They are not detected in large numbers, however, in a really early stage, because this can only be done by taking an X-ray photograph of the chests of men and women before they begin to feel ill. It sounds a tall order, but it is quite a practical measure, at any rate in large establishments, to radiograph all the workers once every six or twelve months, for the purpose of spotting these early cases. If this were done it would give the worker an excellent chance of early treatment and complete recovery, and also cut out the danger of infections to his fellow-worker and resulting loss of production. It must be emphasized, however, that proper treatment of T.B. in industry will not be achieved while the scale of National Health Insurance benefit remains so low. Patients who ought to be under treatment will often remain at work, infecting their workmates and saying goodbye to their own chance of recovery and a healthy life, because a long treatment would condemn them and their families to existence at the P.A.C. level. The only solution is an immediate increase in the cash benefit paid to tuberculous workers under N.H.I. (which would enable them to buy more nutritious *In London the T.B. death-rate rose from 93 to 101 per 100,000 population in the first six months of 1941, compared with 1940, and the rate of new cases from 171 to 213 per 100,000. Total T.B. deaths in England and Wales rose from 26,176 in 1938, to 28,146 in 1940. 34 21/2049